False-positive Rifampin Resistant Results with Xpert MTB/RIF Version 4 Assay in clinical samples with a low bacterial load - Ocheretina, Oksana (Diagn Microbiol Infect Dis, 2016)
We report investigation of 22 TB cases with positive Xpert MTB/RIF result for resistance to Rifampin and “Very Low” MTB detection level. Twelve cases were false positive without rpoB mutations, 2 were false-positives with a silent mutation in rpoB codon T508 and only 10 were true positives.